Factory Europe? Brainier but Not Brawnier - Behar, Alberto; Freund, Caroline (World Bank, Washington, DC, 2016)
While intermediates comprise the majority of total goods trade in the European Union (EU), their share of total trade has remained flat since 1996. This implies that EU enlargement has had a limited effect on the size of Factory Europe. However, enlargement coincides with an increase in Factory Europe’s complexity. Using two new measures of the complexity of intermediates products, we show that internal EU intermediates trade has become more sophisticated and uses more relationship-specific inputs over time and relative to external EU trade. In other words, Factory Europe has become brainier but not necessarily brawnier. There is also an asymmetry. While the 1995 EU members have not become more significant trading partners for the new members, the new members have become a more important source of intermediates for the EU15 and also a more important market. In sum, the structure of EU trade has changed--not only is the EU15 giving the new members a bigger share of its tasks, it is also giving them harder ones.